Economic analysis of soil erosion effects in alley cropping. No-till and bush fallow systems in south west Nigeria - Ehui, Simeon K.; Kang, B.T.; Spencer, D.S.C. (Elsevier, 1990)
Most upland soils in humid and sub-humid tropical Africa are characterized by low inherent fertility and are also susceptible to soil erosion and compaction with cultivation. Based on simulation model, this study uses a capital budgeting approach to determine the profitability of alternative land use systems, taking into account the short and long-run impact of soil erosion on agricultural productivity in southwestern Nigeria. The fallow systems include: (1) two continuous cultivation alley cropping systems with leucaena hedgerows planted at 2 m and 4 m interhedgerows spacings: (2) the continuous cultivation no-till farming system; and (3) two traditional bush fallow systems with a 3-year cropping period in 6- and 12-year cycles. Under a 10 percent discount rate, when no yield penalties are imposed (reflecting the case of population density), the 12-year cycle shifting cultivation system is most profitable, followed by the 4 m alley cropping, the no-till, the 2 m alley cropping and the 6-year cycle shifting cultivation systems. When penalties are imposed on yields due to land being taken out of production because of fallow vegetation (reflecting the case of rising land values), the 4 m alley cropping is most profitable, followed by the no-till, the 2 m alley cropping, the 12- and 6-year cycle bush fallow systems. Thus where access to new forest land is ‘costless’, slight yield from erosion will not detract significantly from the immediate profit advantage of traditional bush fallow systems, with longer fallow periods.